Post-partum Hospital Stay and Mothers' Choices on Breastfeeding and Vaccines: A Chance We Should Not Miss - Morniroli, Daniela; Consales, Alessandra; Riverso, Luana; Colombo, Lorenzo; Bezze, Elena Nicoletta; Sannino, Patrizio; Zanotta, Lidia; Marchisio, Paola; Mosca, Fabio; Plevani, Laura; Giannì, Maria Lorella (Frontiers in Public Health, 2021)
Parents' education and knowledge regarding major topics of children's health, such as nutrition and vaccines, have a paramount role. However, breastfeeding rates in first year of life are lower than recommended, and vaccine hesitancy is progressively spreading. To reverse this harmful trend, healthcare professionals are challenged to promote correct health information. This study aimed to assess newly mothers' knowledge of breastfeeding and vaccinations, and education received on both topics during hospital stay. We performed a cross-sectional survey in the Postnatal Unit of our Center. Mothers of full-term babies with a birthweight >2,500 g were enrolled. Two different questionnaires, one about breastfeeding and one about vaccines, were proposed to the 140 enrolled mothers. Ninety-nine percent of mothers enrolled were aware of breastfeeding benefits, and 92% felt adequately supported by maternity staff. Less than 25% stated to have received sufficient information regarding breastfeeding. Only 20% of mothers received information about vaccines during hospital stay. Healthcare providers were identified as primary, secondary, and tertiary source of information on vaccines by 55, 15, and 30% of mothers, respectively. Healthcare professionals are crucial in informing and educating mothers on breastfeeding and vaccinations. Post-partum hospital stay could be the right time for this critical responsibility.